Highly Selective Methanol Synthesis Using Electrochemical CO2 Reduction with Defect‐Engineered Cu58 Nanoclusters - Sourav Biswas; Tomoya Tanaka; Haohong Song; Masaki Ogami; Yamato Shingyouchi; Sakiat Hossian; Maho Kamiyama; Taiga Kosaka; Riki Nakatani; Yoshiki Niihori; Saikat Das; Tokuhisa Kawawaki; et al. (Small Science)
Atomically precise copper nanoclusters (Cu NCs) exhibit significant potential as catalysts for the electrocatalytic reduction of CO2. However, the range of products achievable with these NCs has been somewhat constrained. This study presents an innovative design strategy to enhance the catalytic activity of Cu NCs by engineering their active sites. These active sites are formed here by introducing defects on cubic Cu NCs through the partial dislocation of Cu atoms at their vertices, which creates surface ligand vacancies. This dislocation further refines the internal cationic geometry by altering cuprophilic interactions, leading to distinct modifications in the edges and vertices of the cubic geometry. These unique Cu(I) atom arrangements within the cluster effectively influence product specificity during electrochemical CO2 reduction. Density functional theory calculations correlate the enhanced selectivity for CH3OH in [Cu58H20(SPr)36(PPh3)7]2+ (Pr = CH2CH2CH3) NC to the increased reactivity of edge Cu atoms in binding CO and CHO intermediates, compared to [Cu58H20(SPr)36(PPh3)8]2+ and [Cu58H20(SEt)36(PPh3)6]2+ (Et = CH2CH3) NCs. Thus, this work underscores the potential of tailored structural designs of atomically precise nanocatalysts in directing electrochemical CO2 reduction toward unconventional products.